The role played by gender, household income and age in factors contributing to consumers’ attitudes towards short message service advertisements - Michael Humbani; Yolanda Jordaan (Communicare)
The exponential growth in the use of mobile phones has seen companies investing heavily in mobile marketing to exploit the advertising opportunities presented by this medium. This study investigated the role that gender, household income and age play with regard to factors contributing to the attitudes of consumers towards SMS advertisements. The contributing factors reviewed in this study are content appeal, perceived personalisation, interactivity of SMS advertisements, attitudes towards advertising in general, consumers’ innovativeness, perceived consumer knowledge, perceived control, fear of spamming, perceived incentives and locationbased advertising. A convenience sample was drawn from staff and students of three private institutions of higher learning. The findings indicate that gender, household income and age tend to affect consumers’ attitudes towards SMS advertisements. More specifically, of all the contributing factors, household income emerged as the most significant differentiator.